Penanggulangan Kerusakan Periodontal Akibat Pemakaian Rubber Ligature (Laporan Kasus) - Sri Oktawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Orthodontic treatment become more popular and interest by the people. Therefore a sufficient knowledge of dentist is very necessary. Improper planning and treatment or using unsuitable equipment wil damage periodontal tissue. If it's happened and untreated carefully as soon as possible, the teeth will fall out. A boy with eight years old got an inflammation and hardly mobility teeth (°4). The condition is happen after using orthodontic rubber ligature to overcome central diastema. Inflammation become harden by leaving of rubber ligature on undetection apical part. A patient got a plaque control, medication, flap operation, temporary and semi permanent splinting. Agter seven month tratment, patient had a minimal inflammation and decreased of mobility teeth until degree two.